The Evolutionary Origin and Genetic Makeup of Domestic Horses. Issue 2 (1st October 2016) - Librado, Pablo; Fages, Antoine; Gaunitz, Charleen; Leonardi, Michela; Wagner, Stefanie; Khan, Naveed; Hanghøj, Kristian; Alquraishi, Saleh A; Alfarhan, Ahmed H; Al-Rasheid, Khaled A; Der Sarkissian, Clio; Schubert, Mikkel; et al.
Abstract: The horse was domesticated only 5.5 KYA, thousands of years after dogs, cattle, pigs, sheep, and goats. The horse nonetheless represents the domestic animal that most impacted human history; providing us with rapid transportation, which has considerably changed the speed and magnitude of the circulation of goods and people, as well as their cultures and diseases. By revolutionizing warfare and agriculture, horses also deeply influenced the politico-economic trajectory of human societies. Reciprocally, human activities have circled back on the recent evolution of the horse, by creating hundreds of domestic breeds through selective programs, while leading all wild populations to near extinction. Despite being tightly associated with humans, several aspects in the evolution of the domestic horse remain controversial. Here, we review recent advances in comparative genomics and paleogenomics that helped advance our understanding of the genetic foundation of domestic horses.